Comparison of remdesivir and favipiravir - the anti-Covid-19 agents mimicking purine RNA constituents - Al-Ardhi, Faiha M.; Novotny, Ladislav; Alhunayan, Adel; Al-Tannak, Naser F. (Biomedical papers, 2022)
By December 2019, humanity was challenged by a new infectious respiratory disease named coronavirus disease of 2019 or COVID-19. This is a viral infection based on the presence of the previously non-problematic coronavirus with assigned number 2. This virus causes severe acute respiratory distress and is known now as SARS-CoV2. Since SARS-CoV2 is an RNA virus, remdesivir and favipiravir, both broad-spectrum RNA polymerase inhibitors, were repurposed for treating COVID-19 patients. Remdesivir and favipiravir are antimetabolites, and they are structurally related to the naturally occurring structural elements of RNA. Both agents are prodrugs and must be activated intracellularly to exert their effects through numerous and different mechanisms of action. Efforts have been exerted to determine their efficacy and safety against COVID-19 through clinical trials. Clinical trials have shown an association of remdesivir with increased frequency of adverse effects (in comparison to favipiravir). Nevertheless, the data obtained with remdesivir resulted in its approval by the FDA on the 22nd of October 2020 for COVID-19 treatment. At present, remdesivir is being recommended by several treatment guidelines for the treatment of COVID-19 patients. The evidence in favor of favipiravir is compromised by the small number and low-quality of trials conducted. Favipiravir has shown various benefits when administered in mild and moderate cases of COVID-19, while remdesivir was more beneficial in more severe cases of the disease. Since the two agents are suitable for different groups of patients, both drugs can play a significant role in fighting this pandemic. The goal of this work is to summarize the information available on two antimetabolites - remdesivir and favipiravir - and to compare clinical experience obtained so far with these two agents in COVID-19 patients.
Keywords: remdesivir; favipiravir; Covid-19; antimetabolites; RNA-polymerase inhibitors; respiratory syndrome